PENINGKATAN KECAKAPAN DIGITAL DALAM PEMBUATAN KONTEN PEMBELAJARAN BERBASIS CANVA BAGI SISWA SMA YAS SINDANGKERTA - Gilang Gumilang Dawous; Satria Andika Al Rasyid; Safaat Safaat (Jurnal Al Maesarah, 2023)
Digitalization is growing rapidly at this time, especially digital platforms used in education. The use of the internet and social media in Indonesia is very massive. Therefore, it is necessary to increase digital skills, especially for students in developing their interests and talents in digital literacy. Digital skills in this activity are carried out by holding digital content creation seminars using the Canva platform as an attractive and easy-to-access digital content creation application. The seminar was held at YAS Sindangkerta High School by involving West Java ICT Volunteers and Student STAI Darul Falah Bandung Barat. This digital content can change students' habits to use the internet wisely and turn negative habits into more productive ones to create digital content of images, music and videos through a variety of digital products to be used in everyday learning life.